Dwa pojęcia świadomości i podmiotu - ZIEMIŃSKA, Renata (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
In contemporary research on the nature of mind there are two basic notions of consciousness: fi rst-person (phenomenal) consciousness and third-person awareness. The fi rst one is the feeling qualities, the second one is reacting to stimuli and processing information. Similarly, we have two concepts of the subject. The subject of phenomenal consciousness is the centre of the stream of consciousness, the agent and owner of all feelings. The subject of awareness is a conscious system, usually a biological organism, carrying on the conscious processes. The naturalistic approach cannot successfully explain how the binding of different data is going on to become the one stream of consciousness with identical I as its centre. The fi rst-person approach cannot successfully explain the identity of consciousness and body. The two perspectives complement each other.